POVERTY IN COMMUNITY SOCIAL AND ECONOMIC DEVELOPMENT PERSPECTIVE - Syahputra, Angga; Rofizar, Henny (Islamic Economics Program, Faculty of Islamic Economics and Business, 2022)
Poverty is a socio-economic problem that has stimulated many research activities carried out by various parties such as planners, scientists, and the general public or non-governmental organizations from various educational backgrounds. The large number of poor people will have the potential to create new social problems, namely the decline in the quality of human resources, the emergence of inequality and social jealousy, disruption of social and political stability and increasing crime rates. The decline in the poor population is not too significant and is still relatively large. The government has struggled continuously to reduce the poor in its area with various strategies. The goal for the welfare of the nation's life seems to be just a discourse. The more widespread planning and development activities have not been able to overcome poverty in Indonesia, so to find alternative future policy solutions in an effort to accelerate poverty alleviation requires thinking from various cross-disciplinary social sciences. The method used in this study is descriptive analysis method, which describes a problem of community poverty based on secondary data sources from literature materials that are relevant to the title of the article and references. The sociological reality of poverty has different criteria, namely absolute and relative and not only personal events but also social events. Regarding religion, Islam responds to the phenomenon of poverty by encouraging and encouraging people to work hard and share with each other. In Islam poverty is explained in the Al-Quran and Hadith where poor people are people who are unable to meet their daily needs.